Energy Efficient Heat Exchange Network for the Oil Vacuum Distillation Facility - Ved V.E.; Ilchenko M.V.; Myronov A.N. (Problems of the Regional Energetics)
The work is related to investigation of the possibility of increasing the energy efficiency of the heat-exchange network of a vacuum distillation unit at a delayed coking facility, as well as an applying the economic effect evaluation practices of the implemented integration measures for the enterprise modernization. The purpose of the work is to increase a thermal energy recovery of a chemical-technological system and to reduce a percentage of external heat carriers in the overall energy consumption structure of the refinery. The task is achieved by applying design algorithms of a pinch analysis. The most important result of the work is the proven possibility of reducing the external heat carriers’ energy by 1.87 MW and increasing the thermal energy recovery inside the system to 11.26 MW. The significance of the obtained results lies in the fact that the final integrational schemas of heat exchange networks can be used for the actual modernization of the observed manufacture, as well as the considered principles can be adapted by engineers of any other processing industry for the sake of production facilities improvement. The tools of composite curves and grid diagrams are used to determine the energy saving potential of the observed system. The cost curves tools carry out the search of an optimal minimum temperature difference value. Final results are provided in the form of a grid diagram of an integrated heat-exchange system. According to the economic assessment of the implementation effectiveness for developed modernization project, the payback period will not exceed three years.